Functional and Structural Plasticity Co-express in a Left Premotor Region During Early Bimanual Skill Learning - Irmen, Friederike; Karabanov, Anke Ninija; Bögemann, Sophie Alida; Andersen, Kasper Winther; Madsen, Kristoffer Hougaard; Bisgaard, Thue; Dyrby, Tim B.; Siebner, Hartwig Roman (Frontiers in Human Neuroscience, 2020)
Introduction: Motor skill learning triggers functional reorganization of regional brain activity already after short periods of training. Recent studies suggest that microstructural change may emerge at similar timescales, but the spatiotemporal profiles of functional and structural plasticity have rarely been traced in parallel. Recently, we demonstrated that five days of endoscopic skill training induced changes in task-related brain activity in the ventral premotor cortex (PMv) and other areas of the ventrolateral grasping network. Here, we analyzed microstructural data, collected during the same experiment, to investigate if microstructural plasticity overlaps temporally and spatially with the training-induced changes in task-related brain activity. Materials and Methods: Thirty-nine students were divided into a full-routine group (n = 20), that underwent three endoscopy training sessions in the MR-scanner as well as a 5-day virtual reality (VR)-endoscopy training and a brief-routine group (n = 19), that only performed the three in-scanner endoscopy training sessions. Diffusion Tensor Imaging (DTI)-derived fractional anisotropy (FA) and resting-state functional magnetic resonance imaging (rs-fMRI) were collected at baseline, after the first and after the last VR-training session. Results: The full-routine group showed significant FA changes in a left-hemispheric subcortical cluster underlying the PMv region, for which we previously had demonstrated functional plasticity during endoscopy training in the same participants. Functional (task-related fMRI) and structural (FA) changes showed the largest change from the first to the second scan, suggesting similar temporal dynamics. In the full-routine group, the FA change in the subcortical cluster underlying left PMv scaled positively with the individual improvement in endoscopic surgery. Conclusion: Microstructural white-matter plasticity mirrors the spatiotemporal profile of task-dependent plasticity task during a five-day course of endoscopy skill training. The observed similarities motivate future research into the interplay between functional and structural plasticity during early skill acquisition.